Critical success factors for R&D leaders - Larson, Charles F.
Charles F. Larson outlines what it takes to become a successful chief technology officer today.
To succeed as an R&D leader; gain-and maintain-credibility by delivering more than you promise, with the help of and through the actions of others.
The role of R&D leaders has evolved into that of a chief technology officer, or CTO, with responsibility for contributing value to the business needs of their companies. Becoming a CTO, however, is not an easy accomplishment. Successful R&D leaders generally were outstanding R&D performers, and are distinguished by a number of traits, among which credibility is foremost. Maintaining credibility in the future will require leaders to leverage internal R&D capabilities with external resources from around the world, to deliver long-term as well as short-term value, to facilitate rapid learning, and to focus on speed in the commercialization of new technology.
Keywords: R&D leaders